The Effect of Service Quality on Customer Loyalty through Customer Satisfaction on the DANA Application in Sumbawa City - Salsabilla Tusaini Harun; Agus Santoso (Escalate : Economics and Business Journal, 2026)
The rapid development of financial technology has led to an increasing use of digital wallet applications in Indonesia, including DANA as one of the widely used cashless payment platforms. However, the growth in the number of users is not always accompanied by strong customer loyalty, given the intense competition among digital wallet providers offering similar features and promotional strategies. This condition encourages companies to continuously improve service quality in orders to enhance customer satisfaction and maintain long-term customer loyalty.This study aims to analyze the effect of service quality on customer satisfaction and customer loyalty, as well as the role of customer satisfaction as a mediating variable among DANA application users in Sumbawa City. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to DANA users in Sumbawa City using non-probability sampling with a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results indicate that service quality has a positive and significant effect on customer satisfaction and customer loyalty. However, customer satisfaction does not have a significant effect on customer loyalty and does not mediate the relationship between service quality and customer loyalty. These findings suggest that although service quality can enhance customer satisfaction, such satisfaction is not sufficient to directly foster long-term customer loyalty.